1975
DOI: 10.2307/3897225
|View full text |Cite
|
Sign up to set email alerts
|

Response of Root and Shoot Growth of Three Grass Species to Decreases in Soil Water Potential

Abstract: Highlight: iVa tive grass species show differences in leaf and root growth response to soil water potential. Soil water potential developed by blue grama at the time of leaf growth stoppage ranged from <-80.0 bars at 5 cm depths to-8.4 bars at 35 cm depths, while corresponding values for little bluestem were-24.3 and-3.0 bars, and-30.0 and-15.3 bars for western wheatgrass. Soil water potentials at the time of root growth cessation were somewhat lower with a minimum of-16.6 bars at the S cm depth of blue grama … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…Seed production would therefore be maximized with enhanced pollination, as both are outcrossing species (Anderson and Aldous, 1938; Riegel, 1941; Miller, 1967). Although Majerus (1975) found that little bluestem did not perform as well as blue grama under low soil moisture conditions, we observed that dryer conditions coinciding with higher temperatures favored little bluestem seed yields, as seen in 1995 (Table 2). Conversely, blue grama seed and culm production under a relatively cooler but wetter season in 1994 was greater than under a dryer and warmer season in 1995.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Seed production would therefore be maximized with enhanced pollination, as both are outcrossing species (Anderson and Aldous, 1938; Riegel, 1941; Miller, 1967). Although Majerus (1975) found that little bluestem did not perform as well as blue grama under low soil moisture conditions, we observed that dryer conditions coinciding with higher temperatures favored little bluestem seed yields, as seen in 1995 (Table 2). Conversely, blue grama seed and culm production under a relatively cooler but wetter season in 1994 was greater than under a dryer and warmer season in 1995.…”
Section: Resultsmentioning
confidence: 59%
“…N ative grasses are important for soil erosion control (Cornelius, 1946) and revegetation of wildlife habitat. Blue grama and little bluestem are dominant warm‐season grass species in the Great Plains (Hitchcock, 1950) and are recognized for their adaptedness and drought tolerance (Majerus, 1975) Use of blue grama and little bluestem is presently limited in western Canada by availability of adapted seed sources. Presently, commercial quantities of blue grama and little bluestem seed are often obtained from U.S. sources where they are sold as cultivars or simply by species name.…”
mentioning
confidence: 99%
“…Mi is equal to one for soil water tension less than -30 bars and decreases linearly to zero at -50 bars. These equations were based on the following assumptions: (i) allocation of photosynthate to roots decreases with soil depth (Singh & Coleman 1974), (ii) relatively higher soil water content in a particular layer will cause more photosynthate to be allocated to that layer (Warembourg & Paul 1973), (iii) high soil water content will cause more of the Ares (1976) and Majerus (1975)]. …”
Section: Aging Of Rootsmentioning
confidence: 99%
“…photosynthate allocated to a layer to be sent to the juvenile roots (Majerus 1975;Ares 1976). Initial estimates for WA and constants in eqns (19), (20) and (21) were based on information in Ares (1976) and Ares & Singh (1974), and were modified during model tuning.…”
Section: Aging Of Rootsmentioning
confidence: 99%
“…It is widely recognized as an important species in a short-grass ecosystem, and is thought to be the most drought and grazing tolerant plant species in the short-grass community. Due to its economic importance and drought-resistance characteristics, this grass has been the subject of intensive ecological and physiological research (Majerus 1975, Brown and Trlica 1977, Monson et al 1986, Aguilera and Lauenroth 1993, Moreno-Gómez et al 2012). The first tissue culture system of blue grama grass was developed by Aguado-Santacruz et al (2001); it was the first report of a chlorophyll (Chl)containing cell suspension from the family Poaceae.…”
Section: Introductionmentioning
confidence: 99%